Behind the scenes of theatrical meaning: a social semiotic approach to inter- and intramodal interactions in performance - Ghazvineh Arash; Fahimifar Asghar (Language and Semiotic Studies)
This article adopts a Social Semiotic perspective to meaning-making in theater, contending that such an approach is essential for comprehensively addressing the intricate interrelations among the diverse sign systems inherent to the theatrical domain. While existing scholarly literature acknowledges the complex nature of meaning construction in theater and underscores the importance of analyzing the interplay between various sign systems, there exists a notable paucity of in-depth explanations regarding the systematic modeling and further exploration of these interrelationships. Recognizing this gap, the present study endeavors to bridge this gap by demonstrating the efficacy of incorporating a Social Semiotic framework into the current discourse on theater semiotics. Through a comparative analysis of English and Persian renditions of Robert Bolt’s play A Man for All Seasons, this research illustrates the applicability of such a perspective in enhancing the understanding of meaning-making in theater as a rich multimodal text. The findings demonstrate that a Social Semiotic framework not only acknowledges the pivotal role of inter- and intramodal interactions in theatrical meaning-making but also offers a comprehensive toolkit for interrogating such interactions more effectively.